STATUS KEBERLANJUTAN DIMENSI EKOLOGI BUDIDAYA IKAN PATIN (PANGASIANODON HYPOPHTHALMUS) DALAM PENGEMBANGAN KAWASAN MINAPOLITAN - Yoyo Wiramiharja; Eddy Supriyono; Ernik Yuliana (LPPM Universitas Terbuka, 2018)
Kumpeh Ulu District is a minapolitan area in Muaro Jambi Regency with main commodity of catfish. The purpose of this study was to analyze the sustainability status of ecological dimension of catfish culture in the development of minapolitan area. The study sites were some villages Kumpeh Ulu District: Pudak, Kota Karang, and Lopak Alai. The research design used quantitative approach. Data collection was done through questionnaires, interviews, and field observations. The population of this research is fishers in Kumpeh Ulu District, and the respondents are 48 fishers. Respondents were determined randomly (simple random sampling). Data were analysed using multidimensional scaling (MDS) with the Rap-Patin device has been modified from the RAPFISH program. The result of analysis to nine attributes obtained by index value is 55,40 and the most sensitive attribute is aquaculture waste processing. The sustainability status of the resulting ecological dimension is